Acute Pancreatitis with Abdominal Bloating and Normal Transabdominal Ultrasound - Halim, Silvikarina Erfanti Dewi (The Indonesian Society for Digestive Endoscopy, 2023)
Acute pancreatitis (AP) is an inflammatory disorder of the pancreas, and its correct diagnosis is an area of interest for clinicians. A 44-year-old man, presented with bloating for 1 month and getting worsened 1 day before admission to emergency room (ER), accompanied by discomfort in the upper left abdomen. The patient had abdominal distension, no vomiting or severe abdominal pain. Ultrasonography (USG) transabdominal revealed polyp gallbladder, no stone or pancreatitis. Magnetic resonance imaging (MRI) 2 months before at the ER, showed multiple stone in gallbladder and normal pancreas. Leukocytes 15 x 103/L, serum glutamic pyruvic transaminase (SGPT) 262, serum glutamic oxaloacetic transaminase (SGOT) 249, gamma glutamyl transferase (GGT) 1369 U/L, total bilirubin (TBIL) 2.44, direct bilirubin (DBIL) 2.08, lipase 14,690 U/L, amylase 3,693 U/L. Patient refused computerized tomography scan (CT scan) or MRI repeated, based on Atlanta criteria, abdominal discomfort with high amylase/lipase and a history of gallstones, the diagnosis was made. After 3 days, SGPT 44, SGOT 19, GGT 732 U/L, lipase 46 U/L, amylase 38 U/L. Based on Atlanta classification, AP diagnosed if at least 2 of the following 3 criteria are fulfilled: abdominal pain, serum lipase or amylase at least 3x the upper limit of normal (ULN) or characteristic findings on imaging. Gallstones are the most cause of AP. Abdominal bloating in this patient couldn’t be explained by common causes, such as ascites, bowel edema, hematoma, ileus which led us to suspect pancreatitis. CT scan contrast or MRI was essential in patients with normal USG and no classic sign abdominal pain.